Investigasi Kejadian Luar Biasa Hepatitis A di Kota Depok - Rahmat Saputra; Nurhayati A Prihartono; Dwi Oktavia TL Handayani; Yeni Devita (HEALTH CARE : JURNAL KESEHATAN, 2021)
Hepatitis A is still an extraordinary event (KLB) nationally in Indonesia. Based on the results of Riskesdsa 2018, the incidence of hepatitis A reached 0.39. The city of Depok, West Java, is also an area with an outbreak of hepatitis A. The purpose of this study is to describe the risk factors that influence the usual occurrence (outbreak) of hepatitis A in Depok City in 2019. The type of research used is an analytical observational study using a case control design. The research population was 705 respondents. Consisting of 318 cases and 387 controls. Risk data factors were obtained from questionnaires given to respondents at SMPN 20 Depok, residents of RT 01 and RT 02/RW 01, RT 3/RW 02, Rangapan Jaya Village and Pesantren Petik. The questionnaire comes from the source of guidelines for handling outbreaks of the Ministry of Health with modified questions. The risk factors that affect the hepatitis A outbreak in Depok City are refill drinking water sources, the habit of not using CTPS before eating, the habit of not using CTPS after defecating and eating/drinking behavior using shared utensils. The source of the Hepatitis A outbreak in Depok City cannot be known with certainty but it will be suspected that the consequences occur red at the same time (general sources). This is supported by an epidemic curve in the form of a point source.